(untitled) (Journal of actual problems of jurisprudence, 2018)
In the given article the author considers the non-tariff regulation of foreign economic activity. It is noted that non-tariff measures are one of the ways of state regulation of foreign trade activities. The author pays attention to the prohibitions and restrictions applicable state. Key words: non-tariff measures, trade, government regulation, prohibitions and restrictions.